The Chapel of St Catherine at the Cistercian Abbey of Savigny: 'unearthing' an architectural enigma - Allen, R (Cambridge University Press, 2023)
This paper examines the evidence relating to the twelfth-century chapel of St Catherine at the Norman abbey of Savigny. It brings together the findings of the latest archaeological survey of the monastic precinct, of which only fragments survive, with a comprehensive analysis of all the available references to – and scholarly discussions of – the chapel, which was destroyed in 1705. In doing so, it looks to shed light on an edifice that, although long known to those with an interest in Savigny, head of Normandy’s only native monastic congregation, nevertheless remains something of a mystery, such that its precise location has, to date, been a matter of conjecture. By building on findings revealed by the first ever geophysical surveys of the site in 2016, this article argues that the chapel’s probable position within the claustral complex was almost unique in the Cistercian world, with its closest parallels being found instead in the Cluniac one. These circumstances were born more of accident than design, but they nevertheless presented challenges for Savigny’s medieval community, who had to manage both benefactor burials in the chapel and pilgrim access to it, the consequences of which help shed light on wider issues relating to the use and reuse of Cistercian monastic spaces.